2021
DOI: 10.1002/jcu.23057
|View full text |Cite
|
Sign up to set email alerts
|

The importance of first trimester screening of cranial posterior fossa in predicting posterior fossa malformations which may be identified in the following weeks of gestation

Abstract: Purpose We aimed to investigate the value of posterior fossa ultrasonography measurements in predicting fetal posterior fossa anomaly at 11–14 weeks of gestation. Methods The study was performed at Zeynep Kamil Women and Children's Diseases Training and Research Hospital. Measurements were made in two groups: the control group consisted of 328 fetuses with normal postnatal outcome and the study group consisted of 22 fetuses with enlarged 4th ventricle. In the study group, we questioned the value of intracrania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…Applying the normal reference ranges of BSOB values obtained from our study to the BSOB measurements listed in the 17 cases of suspected anomalies of the cystic posterior fossa included in the study of P. Volpe et al [ 29 ] revealed that 16 cases were greater than the 95th percentile, which was generally consistent with the 15 cases greater than the 95th percentile obtained in that study. In our study, CM, IT, BS, and BSOB were found to be positively correlated with CRL, and BS/BSOB was negatively correlated with CRL, which was consistent with the results of most investigators [ 13 , 28 , 29 ]. This result suggested that it was reasonable and necessary to establish a normal reference range based on the CRL grouping.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Applying the normal reference ranges of BSOB values obtained from our study to the BSOB measurements listed in the 17 cases of suspected anomalies of the cystic posterior fossa included in the study of P. Volpe et al [ 29 ] revealed that 16 cases were greater than the 95th percentile, which was generally consistent with the 15 cases greater than the 95th percentile obtained in that study. In our study, CM, IT, BS, and BSOB were found to be positively correlated with CRL, and BS/BSOB was negatively correlated with CRL, which was consistent with the results of most investigators [ 13 , 28 , 29 ]. This result suggested that it was reasonable and necessary to establish a normal reference range based on the CRL grouping.…”
Section: Discussionsupporting
confidence: 93%
“…The standard for qualitative diagnosis of the normal posterior fossa structure was to clearly display “three spaces and four lines”, but there is no unified standard for quantitative evaluation of related posterior fossa parameters in China [ 25 27 ]. Eric Ozdemir M et al [ 28 ] demonstrated that IT value, BSOB value, and BS/BSOB ratio were identified as ultrasound variables for predicting posterior fossa anomalies with a sensitivity of 100%, 100%, and 100%; and specificity of 95.9%, 94.7%, and 98.5%, respectively in Istanbul. The largest study on the establishment of a normal reference ranges for parameters related to the posterior fossa was from abroad and included 15,526 pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the study also found that all IT values were higher than the 95th percentile and BS/ BSOB was signi cantly lower than the normal group, and 14 of the 17 cases had DWM or BPC, and/or aneuploidy chromosome abnormalities. Eric Ozdemir M et al [23] included 22 fetuses with fourth ventricular widening and selected parameters consistent with this study, showing that IT value, BSOB value, and BS/BSOB ratio were identi ed as ultrasound variables for predicting posterior fossa anomalies with a sensitivity of 100%, 100%, and 100%; and speci city of 95.9%, 94.7%, and 98.5%, respectively.…”
Section: Discussionsupporting
confidence: 63%